THE INFLUENCE THE INFLUENCE OF PERSON JOB FIT TOWARD JOB SATISFACTION : THE ROLE OF JOB BURNOUT ON PT BANK CENTRAL ASIA OFFICE MAIN BRANCH DIPONEGORO SURABAYA - Ramawati, Yussi (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
This aims of the  research are to determine the effect of person job fit on job satisfaction, person job fit on job burnout and the influence of job burnout on job satisfaction of PT Bank Central Asia employees of Diponegoro Branch Office. Collecting data collection using questionnaires. The sample were front desk employees of PT Bank Central Asia Main Branch Office Diponegoro Surabaya. The analysis method used is Partial Least Square (PLS). The results showed that person job fit has an effect on the job-faction, the person job fit has an effect on job burnout, but job burnout does not effect employeess job satisfaction .Keywords: Person job fit, job burnout, job satisfaction.